Pengaruh Marketing Mix, Lifestyle, dan eWOM Terhadap Brand Image Perusahaan Provider Telekomunikasi di Indonesia Era Digitalisasi Ekonomi - Uliati Nafiah; Risdiana Himmati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The research purpose was to determine the impact of marketing mix, lifestyle, and eWOM on the brand image of telecommunications provider companies in Indonesia on the era of economic digitization, case studies on active students of Sharia Business Management at UIN SATU 2018 generation. The method is quantitative. The sampling technique used was simple random sampling and measured by Slovin formula with an error limit of 5%, 212 students. The data were analyzed by multiple linear regression based on ordinary least squares. The results demonstrate that the marketing mix, lifestyle, and eWOM variables partially and simultaneously influenced the brand image of telecommunications provider companies in Indonesia on the era of economic digitization. Thus, cellular telecommunications provider companies in Indonesia should build a good brand image to increase the credibility of the targeted target market to win a fairly tight competition in the era of economic digitization. Keywords: Marketing Mix; Lifestyle; eWOM; Brand Image